The role of teachers' digital competencies, use intention of online teaching and students' Online learning difficulties in predicting online teaching behavior - Sara Ebrahimi (Shahid Chamran University of Ahvaz, 2022)
Corona epidemics have forced educational systems in many countries to use online education and adapt to digital learning environments.Despite many benefits of online education, such as unlimited time and space,resource sharing and collaboration, openness and personalization of learning,but it can be frustrating and stressful because many teachers lack the skills, resources and competencies of online education.A review of research evidence shows that a large amount of research activity is devoted to teachers' digital competencies, but information on how this feature,along with other teacher features such as use intention of online teaching and student features such as online learning difficulties affects on their online teaching behavior, are not available.Thus,the aim of this study was to investigate whether teachers'digital competencies,use intention of online teaching and students' online learning difficulties predict online teaching behavior.In this correlation study, the population was all teachers of primary and secondary schools in Tehran in the academic year1400-1401,which324teachers were selected with use of convenience sampling.They responded online to the Teachers' Digital Competence Scale,Teachers' Use Intention of Online Teaching Scale,Teachers'Online Teaching Behavior Scale&Teachers'Perceived Online Learning Difficulties of Students Questionnaire.Pearson correlation coefficient and multiple regression analysis were used to analyze the data.The results showed that the online teaching behavior had a positive andsignificant relationshipwith teachers'digital competencies and the use intention of online teaching, and this relationship was negatively and significantlywith students'online learning difficulties.Also, the resultsof multiple regression analysis showed that teachers'digital competencies, use intention of online teaching and students'online learning difficulties, are able tosignificantly explain changes in teachers'online teaching behavior as predictor variable in a predictive model. Based on the research findings, it is necessaryfor teachers in online teaching to improve their digital skills and competencies in accessing and using resources, analyzing data related to students' learning characteristics, and combining digital resourceswith educational content to produce more comprehensible content, in fact, modify and improve online teaching behaviors.Also,online teaching has more requirements for teachers than traditional classroom teaching. People use digital technology and resources to varying degrees;Therefore, it is necessary for teachers in teaching activities to strengthen their desire to use online education and increase their awareness of integrating information technology with educational activities by avoiding mechanical transfer to offline-online education.Overall, the present study adds insights into improving online teaching behavior&can help to better understand the effect of teachers'characteristics including digital competencies and use intention of online teaching and students' characteristics including online learning difficulties on online teaching behavior.